A Bifunctional Nano‐Electrocatalyst Based on a Flower‐Like Gold/Palladium Bimetallic Alloy Nanostructure and Its Graphene Hybrid. Issue 24 (30th November 2015) - Sahu, Subash Chandra; Satpati, Biswarup; Besra, Laxmidhar; Jena, Bikash Kumar
Abstract: The front cover artwork for Issue 24/2015 is provided by the CSIR‐Institute of Minerals and Materials Technology in collaboration with the Saha Institute of Nuclear Physics. The image shows the high performance of a flower‐like Au–Pd alloy nanostructure and its graphene hybrids as bifunctional electrocatalysts towards the oxidation of methanol and reduction of oxygen for fuel applications. See the Full Paper itself athttp://dx.doi.org/10.1002/cctc.201500465 . Abstract : "The development of potential electrocatalysts with robust CO‐poisoning resistance is highly desirable" This, and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttp://dx.doi.org/10.1002/cctc.201500465 .